A study of sports scores based on correlation analysis and logistic regression - Chen, Shaohang; Chen, Jiacheng; Jiang, Ruizhe; Xuan, Yian; Liang, Siming (Transactions on Computer Science and Intelligent Systems Research, 2024)
This paper examines the relationship between "Momentum" and victory in the imbledon 2023 men's tournament, particularly between the semi-finals and the final. The definition and ormula of the Pearson's correlation coefficient are presented, and the Pearson's correlation oefficient is analysed based on the match data between Carlos Alcaraz and Novak Djokovic. The results show that there is a positive correlation between "Momentum" and winning. Then the logistic regression model was used to analyse the factors affecting the variation of "kinetic energy", such as onsecutive points, decisive points, key points, fatigue level and double faults. By training and testing the data set, a logistic regression model was developed for predicting the changes in "kinetic energy", and some suggestions based on the differences in "Momentum" were made to help players and coaches better cope with the changes in "Momentum" in the game. This paper also proposes some suggestions based on "Momentum" differences to help players and coaches better cope with "Momentum" changes in matches.